Hemagglutinin–neuraminidase balance confers respiratory-droplet transmissibility of the pandemic H1N1 influenza virus in ferrets - Yen, Hui-Ling; Liang, Chi-Hui; Wu, Chung-Yi; Forrest, Heather L; Ferguson, Angela; Choy, Ka-Tim; Jones, Jeremy; Wong, Diana Dik-Yan; Cheung, Peter Pak-Hang; Hsu, Che-Hsiung; Li, Olive T; Yuen, Kit M; et al. (Proceedings of the National Academy of Sciences - PNAS, 2011)
A novel reassortant derived from North American triple-reassortant (TRsw) and Eurasian swine (EAsw) influenza viruses acquired sustained human-to-human transmissibility and caused the 2009 influenza pandemic. To identify molecular determinants that allowed efficient transmission of the pandemic H1N1 virus among humans, we evaluated the direct-contact and respiratory-droplet transmissibility in ferrets of representative swine influenza viruses of different lineages obtained through a 13-y surveillance program in southern China. Whereas all viruses studied were transmitted by direct contact with varying efficiency, respiratory-droplet transmissibility (albeit inefficient) was observed only in the TRsw-like A/swine/Hong Kong/915/04 (sw915) (H1N2) virus. The sw915 virus had acquired the M gene derived from EAsw and differed from the gene constellation of the pandemic H1N1 virus by the neuraminidase (NA) gene alone. Glycan array analysis showed that pandemic H1N1 virus A/HK/415742/09 (HK415742) and sw915 possess similar receptor-binding specificity and affinity for α2,6-linked sialosides. Sw915 titers in differentiated normal human bronchial epithelial cells and in ferret nasal washes were lower than those of HK415742. Introducing the NA from pandemic HK415742 into sw915 did not increase viral replication efficiency but increased respiratory-droplet transmissibility, despite a substantial amino acid difference between the two viruses. The NA of the pandemic HK415742 virus possessed significantly higher enzyme activity than that of sw915 or other swine influenza viruses. Our results suggest that a unique gene constellation and hemagglutinin–neuraminidase balance play a critical role in acquisition of efficient and sustained human-to-human transmissibility.